Rationalizing Chinese hegemony - Chang, Yu-Ping (Kansas State University, 2020)
This dissertation examines the Chinese style of imperialism in the early 21st century through China’s self-justifying rationalization and strategic thought. It develops a theory called Cultural Subjectivism to explore the PRC’s preferred world order. Specifically, it analyzes the characteristics of Chinese subjectivity and how Beijing shapes the roles of the self and others through the othering and altercating processes in order to justify the country’s overseas expansion. The international order that Beijing espouses reflects a realistic assessment of world politics. This realpolitik, however, is denied in the narratives for public consumption. Several idealistic principles that China claims are guiding its foreign policy (and devoid of strategic calculations) create a false impression that Beijing is an altruistic actor occupying the moral high ground. Anchoring Chinese behavior to the inherent benevolence of the PRC underpins an unfalsifiable self-justifying logic that, regardless of shifts in policies, Beijing’s behavior is always defensive, peaceful, non-expansionist and non-hegemonic. In accord with Beijing’s assessments of the post-Cold War peace, its narratives have grown more inclusive in that the opposing roles (the othering) between the self and others becomes less salient while the role congruence (the altercasting) that indicates shared interests gets more prevalent. This is tailored to meet China’s strategic needs of the attainment of material strength and international status in the era of post-Cold War globalization through engagement with countries around the world. Paralleling the increasing usage of inclusive rhetoric to rationalize Beijing’s overseas expansion is the growing discursive assertiveness of a China-espoused world order in which Chinese institutions and Chinese culture are said, due to their innate benevolence compared to hegemonic capitalism, to bring the world peace and prosperity. After all, the inclusive narratives and the role (re)construction spin around the concept of Chinese socialism, an embodiment of the PRC’s self-centeredness, and how it is good for both domestic development and international community. Beijing’s role construction operates within a quasi-world-like “Asia Pacific” that includes the Pacific and Indian Oceans and the Eurasian continent. Within this expansive geographical scope, China adopts the grand strategy of “winning without fighting” which consists of the strategies of “cooperation” and limited provocations. The purpose is to amass resources through the land to cope with the challenges from the sea. As the strategic logic of winning without fighting dictates, the PRC intends to achieve its political goals during peacetime while, through disarming enemies and strengthening itself in its overseas expansion, preparing for a possible future war if non-war solutions prove impossible for obtaining its goals. Accordingly, “active defense” needs to be understood as a strategic guideline that directs the generation of resources and abilities for both non-war and war solutions. From a Chinese perspective, regardless of the means adopted, China’s behavior is always defensive and for the sake of peace wherever the activities occur. This unfalsifiable rationalization that relies on the benevolent nature of the self, rather than an admission of realistic calculations, to explain its own behavior functions on a global level and characterizes active defense. From the perspective of discursive rationalization, China exhibits the height of imperialism. Compared to Japan and the US, Beijing shows an unprecedented degree and scale in claiming itself moral in that it is altruistic and inclusive, while firmly believing in its own claims. It is the gulf between complicated realities and the extent of the PRC’s willingness to systematically deny such or cover up what happens on the ground and a lower degree of transparency in its strategic calculations for self-interests that make Chinese imperialism different from others.
Keywords: the height of imperialism; (entrenched) belief; moral high ground (authoritarian inclusiveness and ultra-defensiveness); Chinese institutions and Chinese culture; grand strategy; active defense